Measurement of the Performance of the Sugar Cane Grinding Machine at the XYZ Sugar Factory - Elok Pawening Maharani; Endy Suwondo; Darmawan Ari Nugroho (Agroindustrial Journal, 2021)
XYZ Sugar Factory is a sugar factory which has problems related to the effectiveness of the machines at the sugar cane milling station. This can be seen in the condition of machines that are outdated and in 2013 the level of machine downtime at milling stations tended to increase and exceeded the standard percentage set by the company for the last 3 months. Measurement of machine performance at this milling station uses the Overall Equipment Effectiveness (OEE) method, which is then carried out by measuring six big losses to determine the amount of efficiency lost. From the six factors, it can be identified which factor of losses has the biggest contribution in influencing the level of machine effectiveness by using the Pareto diagram. The data used were data from 12 May - 10 November 2014. During that period, the availability value was 94.72%, the performance value was 90.31%, and the quality was 96.78%, so that the OEE value was 82.95%, which means has not met the best practice OEE value, which is at least 85%. The main factors that affect the effectiveness of the machine are idling and minor stoppages losses, namely the machine is idle due to the time waiting for the sugarcane to enter and the problem of machines outside the milling station.